EXAMINATION BY ELISA OF SERA OBTAINED FROM CHICKEN BREEDER AND LAYER FLOCKS SHOWING EVIDENCE OF FOWL TYPHOID OR PULLORUM DISEASE - Berchieri, A.; Iba, A. M.; Barrow, P. A. (World Veterinary Poultry Assn, 1995)
An indirect ELISA using soluble whole cell antigen was used to screen serum samples obtained from breeder and layer flocks some of which had shown clinical or bacteriological evidence of infection with Salmonella Gallinarum or S. Pullorum. There was good correlation between Salmonella infection and the presence of serum samples showing high optical density (OD) values. Sera from seven flocks showing high values were retested using group D (0-1, 9, 12) lipopolysaccharide (LPS) and g,m-H flagella as detecting antigens. Sera from six flocks produced high OD values with LPS and low values with flagella confirming infection with a non-flagellate, group D Salmonella while one produced high values with both antigens indicating mixed infection with another group D serotype.